Istirātījiyyat Taqdīm al-Ārā’ fī Ta‘līm Mahārat al-Kalām: Dirāsat Ḥālah fī Jam‘iyyat al-Tsaqāfah wa al-Dirāsah al-Islāmiyyah (ICIS) bi-Jāmi‘at Kiyāhī al-Ḥājj Aḥmad Ṣiddīq al-Islāmiyyah al-Ḥukūmiyyah Jember: Opinion Presentation Strategies in Teaching Speaking Skills: A Case Study at the Institute of Culture and Islamic Studies Community (ICIS), Kiai Haji Achmad Siddiq State Islamic University Jember - Washilatul Bariroh; Muhammad Nidom Hamami Abicandra (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2026)
This study examines the implementation of the giving-opinion strategy in teaching Arabic speaking skills to members of the Arabic Language Division of the Institute of Culture and Islamic Studies (ICIS) at Kiai Haji Achmad Siddiq State Islamic University of Jember. It aims to describe the stages of its implementation and identify the supporting and inhibiting factors affecting the process. The study employed a descriptive qualitative approach with a case-study design. Data were collected from the head of the institute, the head of the Arabic Language Division, the advanced-class instructor, and five advanced-class members through non-participant observation, semi-structured interviews, and document analysis. The data were analyzed through data condensation, data display, and conclusion drawing. Their credibility was established through source and technique triangulation and member checking. The findings indicate that the strategy was implemented through several interrelated stages: determining topics and learning objectives, introducing relevant vocabulary and expressions, providing linguistic models, preparing opinions in written form, presenting them orally through discussions, speeches, and academic debates, and conducting correction and evaluation. The main supporting factors included the instructor’s guidance, varied speaking activities, a supportive language environment, and peer support. The inhibiting factors consisted of limited vocabulary, low self-confidence, fear of making mistakes, insufficient speaking practice, differences in learners’ abilities, and limited instructional time. The study concludes that the giving-opinion strategy provides a gradual communicative framework for speaking practice; however, its successful implementation requires adequate linguistic preparation, equitable participation, and continuous practice both inside and outside formal learning sessions.